2021
DOI: 10.1002/ccr3.4210
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear reimplantation from mid‐scala to lateral wall electrode array: Surgical and hearing outcome

Abstract: A mid‐scala cochlear implant electrode array, which was inserted with an atraumatic round window approach, could be replaced with longer lateral wall electrode array. Deeper electrode insertion seems to have beneficial influence on the hearing quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“… 5 The serial technical failure of the device alone does not cause AFNS. 4 Thorough study of his medical record showed that he had a prolonged obstructive hydrocephalus due to the pineocytoma, which was subsequently treated with ventricular drainage. Intracranial hypertension is believed to cause pressure‐induced deossification and is discussed in the literature as a potential cause for superior canal dehiscence 6 and is therefore the most likely cause for the bilateral CFD in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 The serial technical failure of the device alone does not cause AFNS. 4 Thorough study of his medical record showed that he had a prolonged obstructive hydrocephalus due to the pineocytoma, which was subsequently treated with ventricular drainage. Intracranial hypertension is believed to cause pressure‐induced deossification and is discussed in the literature as a potential cause for superior canal dehiscence 6 and is therefore the most likely cause for the bilateral CFD in this case.…”
Section: Discussionmentioning
confidence: 99%
“…An implant check showed the typical constellation of electrophysiological measurements including low electrode impedances in combination with lack of increase in loudness growth perception, suggestive of a delayed technical device failure in a case already published with this implant series. 4 Following detailed unbiased counseling about all technical options and surgical risks, the patient chose to change the device manufacturer and try an alternative electrical stimulation.…”
Section: Case Reportmentioning
confidence: 99%
“… N.S N.S N.S None (IQ > 80) N.S Child N.S Reimplant (1) Mesnildrey [ 32 ] France/UK 1 (1) U (1) N.S N.S N.S N.S 84 AB HiRes 90 k None Nair [ 24 ] India 27 (N.S.) N.S 18:9 N.S N.S None 35 (11–56) N.S None Lyutenski [ 39 ] Germany 1 (2) U (2) 0:1 N.S N.S None 456 492 AB HiRes Ultra with Mid-scala electrode array (1), MED-EL Synchrony 2 with FLEX straight lateral wall electrode array (1) Scalar translocation; implant failure at 3 years and reimplant ‘Impaired’ denotes reported night-blindness or visual field restriction. ‘Blind’ includes legally blind with preserved central vision < 10 degrees and severe visual impairment HA hearing aid; U unilateral insertion; B bilateral insertion—unclear whether simultaneous or sequential; Bsim bilateral simultaneous insertion; Bseq bilateral sequential insertion a Pennings 2006 and Damen 2006, likely include patients reported in Hinderink 1994 and Vermeulen 1994 N.S., not specified, b where age not available, adult, child or mixed population given c median …”
Section: Resultsmentioning
confidence: 99%
“…Speech perception data was reported by 30 studies [ 8 – 10 , 12 , 13 , 15 39 ], using a wide variety of assessment tools (Online Resource 3). Most patients demonstrated improved speech perception, either closed or open set recognition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation